(untitled) (Revista de Administração, 2017)
The objective of this study is to identify external motivating factors that favor individual money donation. Methodologically, we adopted a descriptive and quantitative cross-sectional study. In order to collect data, we prepared a questionnaire containing 49 statements based on external motivating variables of regular individual money donation found in the literature on the subject. After testing the questionnaire, we applied it to 1073 Brazilians, regular money donors and we performed an exploratory factor analysis. Conclusively, we identified 8 external factors that motivate individual money donation: Trust, Reward, Leadership influences, Characteristics of the organization, Environmental influences, Personal benefits, Characteristics of beneficiaries and Future Interests. We expect that these 8 factors combined, could become a useful tool to improve the management of charitable organizations, especially in defining campaigns or other marketing strategies to attract new donors and raise funds on occasions that are favorable to individual money donation.